2013
DOI: 10.1080/01635581.2013.741758
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein, a Secoiridoid Derived from Olive Tree, Inhibits the Proliferation of Human Colorectal Cancer Cell Through Downregulation of HIF-1α

Abstract: Oleuropein (OL) is the most prominent phenolic compound in the fruit of olive tree. Although OL has shown powerful anticancer activity the underlying action mechanism remains largely unknown. The present study evaluated the effects of OL on hydroxityrosol (HT)-29 human colon adenocarcinoma cells in comparison to hydroxytyrosol, its hydrolysis product, and to elucidate the underlying anticancer molecular mechanisms involved. Cell proliferation was determined using SRB assay. Cell cycle and apoptosis were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
90
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 29 publications
8
90
1
1
Order By: Relevance
“…Cardeno et al (14) reported that oleuropein limited cell growth and induced apoptosis in HT29 colorectal cancer cells through a p53-dependent pathway (14). A similar mechanism was also observed in breast cancer cells (12).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Cardeno et al (14) reported that oleuropein limited cell growth and induced apoptosis in HT29 colorectal cancer cells through a p53-dependent pathway (14). A similar mechanism was also observed in breast cancer cells (12).…”
Section: Discussionmentioning
confidence: 76%
“…Andreadou et al reported that oleuropein is involved in cardiomyocyte metabolism through the activation of AMP-activated protein kinase α (AMPK) and suppression of inducible nitric oxide synthases (iNOS) (11). It has recently been reported that oleuropein may have therapeutic potential in a number of types of cancer, including breast cancer (12), thyroid cancer (13) and colorectal cancer (14), via inhibition of cell growth induction of apoptosis. However, to date the effects of oleuropein on liver cancer remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…2, oleuropein induced accumulation of cells in the G 2 /M phase of the cell cycle, when the concentration of oleuropein was over 150 mM. However, some reports suggest that oleuropein induces G 1 arrest in several cell lines, including MCF-7, A549, and HT-29 cells (16,18,62). In MCF-7, olive leaves extract-treated cells was at G 1 arrest by the down-expression of Pin1 and c-Jun (66).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, oleuropein has been investigated for its potent anti-cancer activity. It has been shown to inhibit proliferation and migration of a number of advanced grade human tumour cell lines in a dose dependent manner [6][7][8][9][10][11]. However, the effect of olive phenolic compounds has yet to be investigated for pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%